Assessing Bias and Accuracy in the World Bank-IMF's Debt Sustainability Framework for Low-Income Countries - Berg, Andrew (IMF Working Papers; Working Paper ;, 2014)
The World Bank and the IMF have adopted a debt sustainability framework (DSF) to evaluate the risk of debt distress in Low Income Countries (LICs). At the core of the DSF are empirically-based thresholds for each of five different measures of the debt burden (the 'debt threshold approach' DTA). The DSF contains a rule for aggregating the information contained in these five different variables which we label the 'worst-case aggregator' (WCA) in view of the fact that the DSF considers a breach of any one of the thresholds sufficient to indicate a high risk of debt distress. However, neither the DTA nor the WCA has heretofore been subject to empirical testing. We find that: (1) the DTA loses information relative to a simple proposed alternative; (2) the WCA is too conservative (predicting crises too often) in terms of the loss function used in the DSF; and (3) the WCA is less accurate than some simple proposed alternative aggregators as a predictor of debt distress.